Comprehensive molecular insect science - Gilbert, Lawrence I. (Lawrence Irwin), 1929-2017.; Iatrou, Kostas; Gill, Sarjeet S.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 2005)
Comprehensive reference text on molecular insect science. Includes coverage of developments, achievements and new technologies in modern insect science.
v. 1. Reproduction and development -- v. 2. Development -- v. 3. Endocrinology -- v. 4. Biochemistry and molecular biology -- v. 5. Pharmacology -- v. 6. Control -- v. 7. Indexes.
Title from homepage (viewed Oct. 28, 2005).
Earlier edition published under title: Comprehensive insect physiology, biochemistry, and pharmacology.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Insects -- Molecular aspects; Insecta -- physiology; Insectes -- Physiologie; Insects -- Molecular aspects; Electronic books